Work-life balance, employee value proposition and retention of employees - Moorthi, Manivannan Tachina (2017)
One of the major challenges faced by corporate entities is related to employee retention. Previous studies on employee retention were mostly focused on job satisfaction, compensation, benefit programs, training and development. There is an apparent dearth of literature on work-life balance programs. The scanty works available in this domain cover only flexible benefits and flexible work arrangements. No major study has evaluated the significance of employee value proposition as a contributing factor to work-life balance programs and retention of critical talents. This elevates the importance of the research in this area. This study aim to improve the understanding of the relationship between the work-life balance programs and talent retention in multinational organizations with employee value proposition as a contributing factor. The organization chosen for this study was Lumileds Malaysia Sdn. Bhd. The qualitative approach was chosen for this study, predominantly using interviews and focus group discussion. The personal interaction was important to understand why the employee engagement programs in Lumileds were facing challenges. Based on the previous studies, the result of this study was expected to imply that work-life balance programs make a significant contribution to employee well-being and to the ability of employees to balance their work and personal lives. However, the research finding shows that there were other elements in play that diluted the impact of their engagement programs. The added value would be the identification of the contribution and extent of contribution from employee value proposition to strengthen the impact of the worklife balance program on retention. Consequently, the finding is expected to have an implication for the organizations and human resource practitioners who want to develop comprehensive work-life policies on improving work-life balance, increasing their job satisfaction and retaining critical talents.